2017
DOI: 10.1155/2017/7518789
|View full text |Cite
|
Sign up to set email alerts
|

NPHS2Mutations: A Closer Look to Latin American Countries

Abstract: Nephrotic syndrome is one of the most common kidney pathologies in childhood, being characterized by proteinuria, edema, and hypoalbuminemia. In clinical practice, it is divided into two categories based on the response to steroid therapy: steroid-sensitive and steroid resistant. Inherited impairments of proteins located in the glomerular filtration barrier have been identified as important causes of nephrotic syndrome, with one of these being podocin, coded by NPHS2 gene. NPHS2 mutations are the most frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
0
9
0
1
Order By: Relevance
“…Therefore, genetic testing aids the clinicians to guide the pharmacological treatment avoiding exposure to drugs that would only contribute to unnecessary toxicity and consider the renal transplant in those patients with a genetic origin of steroid-resistant nephrotic syndrome (SRNS) (28,29). Nonetheless, scarce data is available about the prevalence of NPHS2 mutations in pediatric Latin American patients (30). In our study, no pathogenic variants in NPHS2 were found and most of the observed polymorphisms were previously reported and classified as benign.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, genetic testing aids the clinicians to guide the pharmacological treatment avoiding exposure to drugs that would only contribute to unnecessary toxicity and consider the renal transplant in those patients with a genetic origin of steroid-resistant nephrotic syndrome (SRNS) (28,29). Nonetheless, scarce data is available about the prevalence of NPHS2 mutations in pediatric Latin American patients (30). In our study, no pathogenic variants in NPHS2 were found and most of the observed polymorphisms were previously reported and classified as benign.…”
Section: Discussionmentioning
confidence: 99%
“…NPHS2 gene harbors 8 exons and encodes podocin, an interrelated protein with nephrin. Some mutations in the coding sequence of gene may alter its structure and stability and thus, disrupt its functional association and cause proteinuria (45). NPHS2 mutations are associated with infantile-onset, SRNS accompanied by FSGS, and progression to renal failure.…”
Section: Podocinmentioning
confidence: 99%
“…Previous studies claim that incidence of NPHS2 mutations in children may vary according to ethnicity (Thomas et al 2018;Guaragna et al 2017). In 2013 Basiratnia et al (Basiratnia et al 2013) showed that NPHS2 mutations were about 31%, responsible for 57% and 26% of sporadic and familial forms of SRNS.…”
Section: Whole Exome Sequencing (Wes)mentioning
confidence: 99%